2011
DOI: 10.1002/chem.201003278
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Reduction of Olefins by In Situ Generation of Diimide with Synthetic Flavin Catalysts

Abstract: A versatile reducing agent, diimide, can be generated efficiently by the aerobic oxidation of hydrazine with neutral and cationic synthetic flavin catalysts 1 and 2. This technique provides a convenient and safe method for the aerobic reduction of olefins, which proceeds with 1 equiv of hydrazine under an atmosphere of O(2) or air. The synthetic advantage over the conventional gas-based method has been illustrated through high hydrazine efficiency, easy and safe handling, and characteristic chemoselectivity. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 92 publications
2
36
0
2
Order By: Relevance
“…Reactions with MPC catalyst 1 generally proceeded much faster than those with non‐supported catalyst 3 , which indicated the higher catalytic activity of 1 over the full range of concentrations (Figure 6 a–d). The clear dependence on [NH 2 NH 2 ⋅ H 2 O] 0 and the lack of dependence on [styrene] 0 in the reactions with catalyst 3 (Figure 6 b and d) indicated that nucleophilic addition of hydrazine to the oxidized form of the neutral flavin was the rate‐determining step for the overall catalytic process, as described in our previous report 13c. In the reactions with catalyst 1 , a strong concentration dependency on [NH 2 NH 2 ⋅ H 2 O] 0 was observed over the full range of concentrations (Figure 6 a), with dependency on [styrene] 0 at concentrations lower than 1.0×10 −1 M (Figure 6 c).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Reactions with MPC catalyst 1 generally proceeded much faster than those with non‐supported catalyst 3 , which indicated the higher catalytic activity of 1 over the full range of concentrations (Figure 6 a–d). The clear dependence on [NH 2 NH 2 ⋅ H 2 O] 0 and the lack of dependence on [styrene] 0 in the reactions with catalyst 3 (Figure 6 b and d) indicated that nucleophilic addition of hydrazine to the oxidized form of the neutral flavin was the rate‐determining step for the overall catalytic process, as described in our previous report 13c. In the reactions with catalyst 1 , a strong concentration dependency on [NH 2 NH 2 ⋅ H 2 O] 0 was observed over the full range of concentrations (Figure 6 a), with dependency on [styrene] 0 at concentrations lower than 1.0×10 −1 M (Figure 6 c).…”
Section: Introductionsupporting
confidence: 68%
“…As part of our program aimed at new types of catalysts bearing enzyme‐like functions, we are investigating the formation of novel synthetic flavin catalysts with artificial reaction cavities for high efficiency and substrate specificity. Association complexes of neutral flavins with 2,6‐bis(dibenzyloxyamino)pyridines bearing 3,5‐dialkoxy‐13c and 3,4,5‐trialkoxybenzyl ether14 dendron units have proven to act as efficient supramolecular organocatalysts for the highly substrate‐specific aerobic reduction of olefins. In an attempt to develop a new enzyme‐like catalyst, monolayer‐protected gold clusters (MPC)15 have been selected as a new platform for next‐generation synthetic flavin catalysts owing to their high potential for the design and construction of artificial reaction cavities on the nanoparticle surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Such a substrate‐specificity has never been observed with typical flavin catalysts with weak aggregation properties, as indicated by the almost same reaction rates for 2–4 observed for reduction with the non‐gelled flavin catalyst 1 b (Figure b). The lumiflavin ( 5 )‐benzyl ether dendrimer association complex 5 ⋅ G3PAP (Figure b) catalyst exhibits significant substrate specificity for the hydrogenation of 2–4 ; however, the order of the reaction rate ( 2 < 3 < 4 ) is completely opposite to that with gel catalyst 1 a (Figure c). This is a quite rare case of catalysis, where the substrate specificity can be significantly controlled by variation of the association/aggregation mode of the catalyst.…”
Section: Resultsmentioning
confidence: 97%
“…One of our major interests is to create novel flavin catalysts that bear enzyme‐like reaction cavities that are circumferentially arranged at the catalytically active center of a hydroperoxy flavin . Catalytic activities for the oxidation of sulfides,,,, and 1‐benzyl‐1,4‐dihydronicotinamide, Baeyer‐Villiger oxidation of cyclic ketones, and hydrogenation of olefins,, are reportedly enhanced by employing synthetic flavin catalysts that have been modified covalently,,, and non‐covalently with dendrimers,, tripeptides, Au nanoparticles, and cyclodextrins that mimic enzymatic reaction sites.…”
Section: Introductionmentioning
confidence: 99%
“…These products include carbohydrates [12], many antibiotics [13], vitamins [14,15], and steroidal hormones [16,17]. Worth emphasizing is also extensive use of vic-diols in organic chemistry as chiral building blocks [18] and controllers in asymmetric processes [19]; and, 2 vic-diols, as compounds transparent in the UV-vis spectral range, appear to be particularly suitable for application of the VCD spectroscopy method.…”
Section: Introductionmentioning
confidence: 99%